Stealing celestial fire [artificial lightning]. - Predd, P.P.
By shining powerful laser pulses between two electrodes, a group of French and German scientists found that they can elicit a controllable form of lightning. Using pulses from the Teramobile laser, electrons are ripped from air molecules creating a plasma and the refractive index of the air is changed, a phenomenon called the Kerr effect. The effect focuses the light just enough to balance plasma-induced diffraction, creating a straight and highly conductive channel, called a filament, which can stretch up to 3.8 meters between the charged electrodes. The scientists hope that their invention will eventually help to fend off lightning strikes on airports and power stations.
Keywords: Kerr effect; Charged electrodes; Electrode; Lightning bolt; Plasma-induced diffraction; Powerful laser pulse; Refractive index; Teramobile laser